Fast contingency screening for voltage stability analysis considering both SNBs and SIBs - Neves, Lucas Sales; Alberto, Luís Fernando Costa; Chiang, Hsiao-Dong (Electric power systems research, 2022)
Polynomial extrapolation usually leads to crude approximations of the so-called nose curves due to the nonlinear nature of power system operational limits. In particular, these polynomial approximations fail to obtain estimates of the voltage stability margin when the system is subject to structure-induced bifurcations. This paper proposes smoothing out power flow equations to deal with structure-induced bifurcations and verifies the validity of a quadratic approximation of a smooth nose curve in estimating load margin for contingency screening and ranking in voltage stability analysis. Tests of the proposed method in large power systems revealed that an appropriate smooth power flow model can indeed result in better estimates of the exact contingency ranking as compared to the estimates obtained with the original power flow equations. •A smooth formulation of the power flow equations can improve the estimation of VSM.•Both accuracy and speed can be controlled by means of a scalar parameter.•Smoother equations are faster to solve and produce a better contingency ranking.